2019
DOI: 10.1101/741678
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GLAMbox: A Python toolbox for investigating the association between gaze allocation and decision behaviour

Abstract: Recent empirical findings have indicated that gaze allocation plays a crucial role in simple decision behaviour. Many of these findings point towards an influence of gaze allocation onto the speed of evidence accumulation in an accumulation-to-bound decision process (resulting in generally higher choice probabilities for items that have been looked at longer). Further, researchers have shown that the strength of the association between gaze and choice behaviour is highly variable between individuals, encouragi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Extending recent reports (Smith & Krajbich, 2018), we found substantial individual differences in the relationship between gaze and choice behavior. This finding emphasises the importance of modeling these individual differences, in line with recent proposals (Molter, Thomas, Heekeren, & Mohr, 2019). Critically, we found that AQ predicted a weaker relationship between gaze and choice behavior.…”
Section: Discussionsupporting
confidence: 89%
“…Extending recent reports (Smith & Krajbich, 2018), we found substantial individual differences in the relationship between gaze and choice behavior. This finding emphasises the importance of modeling these individual differences, in line with recent proposals (Molter, Thomas, Heekeren, & Mohr, 2019). Critically, we found that AQ predicted a weaker relationship between gaze and choice behavior.…”
Section: Discussionsupporting
confidence: 89%
“…The aDDM is based on the extensively studied drift diffusion model [33,34] and describes how a relative decision value evolves over time, and crucially, how it is biased by overt attention such that ultimately, one item is valued more highly and preferred over another. The approach has influenced a number of groups [35][36][37], but it should be noted that the locus of attention in the model is determined by overt attention (i.e., gaze position) and not by controlling for covert attention, which might sometimes be deployed elsewhere [38]. Whether or not manipulations of covert attention influence preference similarly to manipulations of overt attention is an important open question.…”
Section: Manipulations Of Gaze Influence Preferencementioning
confidence: 99%
“…The GLAM (Thomas et al, 2019;Molter et al, 2019) assumes that choices are driven by the accumulation of noisy evidence in favor of each available choice alternative i. A choice is determined by the first accumulator that reaches a common pre-defined decision boundary b, which we set to 1.…”
Section: Gaze-weighted Linear Accumulator Model (Glam)mentioning
confidence: 99%